RF2 Do people in more deprived areas have a higher risk of alcohol-related hospital admission, after accounting for individually record-linked data on alcohol consumption and smoking?. (September 2018) - Gartner, A; Paranjothy, S; Trefan, L; Moore, S; Akbari, A; Kennedy, J; Fone, D; Farewell, D
Abstract : Background: Greater area deprivation is associated with a higher risk of alcohol-related harm. Few studies have investigated longitudinal patterns of harm using record-linked alcohol consumption, and none considered drink type which is associated with deprivation. This study aims to investigate whether the type of drink is associated with the observed higher risk of alcohol-related hospital admission (ARHA) in people living in deprived areas. Methods: A total of 11 229 people aged 16 and over responded to the Welsh Health Survey in 2013 and 2014, consenting to data linkage. Responses were record-linked within the Secure Anonymised Information Linkage Databank (SAIL) to wholly attributable ARHA (defined by Public Health England) 8 years before the survey month until the end of 2016. They were censored for death or leaving Wales using the Welsh Demographic Service. To each lower super output area (LSOA) at survey month we linked the Welsh Index of Multiple Deprivation 2011, grouping the two more deprived quintiles and three less deprived quintiles. Alcohol consumption and smoking status throughout the study period were estimated from survey responses. We estimated hazard ratios (HR) with 95% confidence intervals (95% CI) for the risk of (multiple) ARHA for deprivation groups using age-based recurrent-event models. The study period started 3 years before the survey. The first model adjusted for sex, time since the last and number of historic ARHA during 5 years before study start. The second model also adjusted for the number of units reported by drink type (beer and cider; wine and champagne; spirits including alcopops) on the heaviest drinking day in the past week and smoking status. Results: 131 respondents had at least one ARHA. People living in more deprived areas had a higher risk of ARHA (HR 1.52; 95% CI 1.08 to 2.14) compared to less deprived. In model 2, adjustment for units of alcohol drunk and smoking reduced the risk of ARHA for more deprived areas (HR 1.29; 95% CI 0.90 to 1.84) with smoking and historic admission having particularly strong effects. Unit increases of spirits drunk were positively associated with increasing risk of ARHA (HR 1.05; 95% CI 1.01 to 1.10), higher than for other drink types. Conclusion: Respondents living in more deprived areas had only a slightly higher risk of alcohol-related hospital admission, considering similar unit consumption, smoking and historic admission. Although significant, adjusting for units by type of drink did not markedly change the socioeconomic pattern of alcohol-related harm.